An Investigation into the Impact of Digital Social Media on the Writing and Speaking Skills of Tertiary Level Students in one Institution in Lesotho - Sekoai Elliot Nkhi (UIR Press, 2023)
This study set out to explore the impact of digital social media on the writing and speaking skills of English as second language tertiary level students in one institution in Lesotho. Current research stipulates that digital social media can have a negative impact on students’ grammatical competence if not used properly. However, digital social media has also been found to have a positive impact on students’ productive skills. In order to find out the impact of digital social media on students’ written and oral skills, the study adopted a qualitative approach confined in a case study. Face-to-face interviews with five (n=5) lecturers and focus group discussions with sixty (n=60) students were used as tools for data collection. Findings from face-to-face interviews with lecturers reveal that digital social media has a negative impact on students’ grammatical competence because they employ short forms in formal writings. Furthermore, findings from group discussions with students reveal two things; firstly, they point to digital social media as having a positive impact on their speaking skills, and secondly as having an adverse impact on their writing skills because of the informal language used in the social media platforms. These findings suggest that students should be taught how to properly use the platforms in order to balance the two skills. The study consequently concludes by recommending that lecturers should constantly encourage their students to chat using formal language all the times especially amongst themselves as this will help them to improve their writing skills.